Role of coblation in reducing pain and morbidity of adenoidectomy - Thomas, George; Thekkethil, Jathin Sam; Thomas, Sumin Mariyam; Ramesh, Shary; Varghese, Ann Mariam (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Adenoidectomy is one of the most commonly performed paediatric surgical procedure by otorhinolaryngologists. Over the past few decades, adenoidectomy has evolved and different techniques have been proposed to reduce morbidity and surgical risk. Controlled ablation or Coblation® is capable of low temperature molecular disintegration within soft tissue causing its dissolution. In this study, we report our experience of adenoidectomy using Coblation®, and its role in reducing pain, morbidity and its significant outcomes are discussed. Methods: A total number of 25 children aged 3-15 years, who underwent coblation adenoidectomy between March 2017 and April 2018 were included in this study. Results: The mean age was 7.8 years (males 7.79 years and females 7.81 years). Pre operatively 100% patients had sleep disturbance and after coblation adenoidectomy only 12% patients have disturbed sleep and the rest 88% patients have comfortable sleep. 80% patients did not have pain in immediate post-operative period and 88% had no pain when they visited hospital for first review. 76% patients had less than one day of hospital stay and 24% patients had more than one day of hospital stay. 68% patients had no episode of upper respiratory tract infection (URTI) within the first one year after surgery. Conclusions: Over the years, many different adenoidectomy techniques have evolved and is surgeon specific or centre specific. Endoscopic-assisted coblation adenoidectomy is a safe and effective method of adenoidectomy.